Spray droplet impaction models and their use within AGDISP software to predict retention - Forster, W.A.; Mercer, G.N.; Schou, W.C. (New Zealand Plant Protection, 2012)
The retention and distribution of spray droplets within the plant canopy have a crucial effect on the biological efficacy of pesticides To maximise spray retention droplets that impact a leaf must remain on the plant Three outcomes are possible when a droplet impacts a leaf surface adhesion bounce or shatter Those droplets that bounce or shatter can continue their journey through the canopy depositing at lower levels in the canopy or on the ground Mathematical models based on the physical processes involved in the bounce/ adhesion and shatter of droplets have been developed improved and described These processbased retention models have recently been implemented within an experimental build of the spray application simulation software AGDISP This has allowed differences in total spray retention to plants due to the spray formulation used or vegetative species studied to be predicted This paper discusses these new tools illustrates the effect different spray formulations and application parameters have on predicted retention and compares model predictions with measured retention